Personal effects : the social character of scholarly writing - Holdstein, Deborah H., 1952-; Bleich, David (Utah State University Press, 2001)
In Personal Effects, Holdstein and Bleich compile a volume that cuts across the grain of current orthodoxy. These editors and contributors argue that it is fundamental in humanistic scholarship to take account of the personal and collective experiences of scholars, researchers, critics, and teachers. With this volume, then, these scholars move us to explore the intersections of the social with subjectivity, with voice, ideology, and culture, and to consider the roles of these in the work of academics who study writing and literature. Taken together, the essays in this collection c.